Capítulos de uma história: a decisão do STF sobre união homoafetiva à luz do direito como integridade - MAUÉS, Antonio Gomes Moreira (Universidade Federal do Pará, 2018)
This work analyses the STF ruling that recognized same-sex unions, based on law as integrity theory of R. Dworkin and on documentary research about the subject. It criticizes the use of legislative intent as a ground to conclude that the Constitution prohibits same-sex unions and argues that the construction of the right to equality in the field of sexual orientation in Brazilian law authorizes the judiciary to recognize these unions.